The biocompound method in coronary artery bypass operations: surgical technique and 3-year patency - Zurbrügg, Heinz Robert; Knollmann, Friedrich; Musci, Michele; Wied, Markus; Bauer, Matthias; Chavez, Tito; Krukenberg, Andreas; Hetzer, Roland (The Annals of thoracic surgery, 2000)
Background. Complete arterial revascularization may be unsafe in patients with a high operative risk. In patients with varicose ectatic veins, the biocompound technique, which uses unsuitable autologous veins, enables the surgeon to influence the bypass graft wall stress levels and diameter. This report summarizes the 3-year patency of 53 patients, the survival rate of 200 patients, and operative technical considerations. Methods. Biocompound grafts were used for aortocoronary bypass in 200 patients who were considered inappropriate subjects for complete arterial revascularization and who had unsuitable saphenous veins. Results. The mortality rate (30 days) of 200 patients was 3.5%. The 3-year survival rate was 88.5%. The patency rate of the left internal thoracic artery (LITA) after 3 years was 97.3%, of the native vein was 68.7%, and of the biocompound graft was 68.3%. The LITA showed a superior patency rate ( p = < 0.05). Conclusions. The LITA is the first choice in coronary bypass operation. The biocompound technique is a reliable method to achieve complete revascularization in patients with a lack of suitable saphenous veins.